Speech By Y.B. Tan Sri Fatimah Bte Haji Hashim,At The Official Opening Of The Fifth General Meeting Of The National Council Of Women's Organisation At Dewan Al-Malik Faizal,Faculty Of Islam,Univeriti Kebangsaan Petaling Jaya,On Saturday,26th August,1972 At 9.30 Am. - Hashim, Fatimah (1972)
It gives me great pleasure to be once again with you all this morning to speak at the General meeting of the National Councll of Women’s Organisations Malaysia.